Edge-effect-mediated microfluidics for fabrication of microporous membrane with well-defined size and shape. (1st February 2019) - Jiang, Chengbao; Li, Xiangming; Shao, Jinyou; Tian, Hongmiao; Li, Xiangmeng; Zhang, Jihang
Abstract: Microporous membranes of well-defined porous size, shape, and distribution are significantly important for environmental engineering and biomedical treatment applications, where high-throughput precise filtration is required. However, efficient manufacturing of desired microporous membranes remains a great challenge. In this study, an cost-effective method, based on edge-effect-mediated microfluidics, is proposed for the fabrication of polymeric microsieves with well-defined micropore arrays. This method refers to a lateral spreading of a liquid prepolymer between the protruding parts of a template and the flat surface of a substrate. The edge effect enables the liquid prepolymer to bypass, instead of filling the microholes of the template. Based on the proposed method, two types of monodisperse SiO2 microspheres were separated by solution filtration.